High excess costs of infections caused by carbapenem-resistant Gram-negative bacilli in an endemic region. (2023)
The financial burden of antibiotic resistance is a serious concern worldwide. The aim of this study was to describe the excess costs associated with pneumonia, bacteraemia, surgical site infections and intra-abdominal infections (IAIs) caused by carbapenem-resistant Gram-negative bacilli in Medellín, Colombia, an endemic region for carbapenem resistance. A cohort study was conducted in a third-level hospital from 2014-2015. All patients with carbapenem-resistant and carbapenem-susceptible Gram-negative bacterial infections were included. Pharmaceutical, medical and surgical direct costs were described from the health system perspective. Excess costs were estimated from generalised linear models with gamma distribution and adjusted for variables that could affect the cost difference. A total of 218 patients were enrolled, 48 (22.0%) of whom were infected with carbapenem-resistant bacteria. IAIs were the most frequent. The adjusted total excess cost was US$3966 [95% confidence interval (CI) US$1684-6249], with a significantly higher cost for antibiotics, followed by hospital stay, laboratory tests and interconsultation. The highest excess cost was attributed mainly to the use of broad-spectrum antibiotics (US$1827, 95% CI US$1005-2648), followed by length of hospital stay (US$1015, 95% CI US$163-1867). The results of this study highlight the importance of designing antimicrobial stewardship programmes and infection control strategies in endemic regions to reduce the financial threat of antimicrobial resistance to health systems.